1999
DOI: 10.1136/hrt.81.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiorespiratory fitness, psychological wellbeing, quality of life, and vocational status following a 12 month cardiac exercise rehabilitation programme

Abstract: Objective-To examine and evaluate improvements in cardiorespiratory fitness, psychological wellbeing, quality of life, and vocational status in postmyocardial infarction patients during and after a comprehensive 12 month exercise rehabilitation programme. Subjects-The sample population comprised 124 patients with a clinical diagnosis of myocardial infarction (122 men and two women). Interventions-62 patients were randomly allocated to a regular weekly aerobic training programme, three times a week for 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 28 publications
0
67
0
14
Order By: Relevance
“…Dugmore reported that AMI patients treated with IVCT are significantly less able to work 4 months after AMI 5) . Brown reported that physical and mental QOL scores are lower 1 month after AMI in patients treated with IVCT because of sleep pattern disturbance and anxiety about reinfarction 6) .…”
Section: Discussionmentioning
confidence: 99%
“…Dugmore reported that AMI patients treated with IVCT are significantly less able to work 4 months after AMI 5) . Brown reported that physical and mental QOL scores are lower 1 month after AMI in patients treated with IVCT because of sleep pattern disturbance and anxiety about reinfarction 6) .…”
Section: Discussionmentioning
confidence: 99%
“…[102][103][104] Patients in the CR cohort also demonstrated a tendency to return to work sooner than those in the conventional care group. 105 Although most trials reported improved HRQoL with CR, meta-analyses were generally unavailable due to heterogeneity in the outcome measures used and varied data reporting. 87,95 Among patients with CHD, those who undergo percutaneous coronary intervention may experience higher HRQoL when compared with CABG over the short term, but the beneficial effects of CR for these patient subsets appear comparable at 2 years.…”
Section: Health-related Quality Of Life and Psychosocial Stress In Camentioning
confidence: 99%
“…Die Wiedereingliederung in den Beruf ist mit einer Verbesserung des psychischen Wohlbefindens assoziiert und die kardiologische Rehabilitation verbessert die berufliche Wiedereingliederung [58,75,153,157,378,[392][393][394].…”
Section: Sozialer Bereich Evidenzunclassified